Stepping stones between two conflicting worlds: the experience of interpersonal communication amongst self-identified problematic internet users - Harland, Ellie (2019)
In the 21st century, we use the Internet to communicate at a level unprecedented in human history. As a result, parallel to worldwide growth in Internet use, there are emerging concerns of its impact on our lives, with much research highlighting social implications. There is controversy within the relevant research literature, as to whether Internet use decreases or increases social connection and as to its psychological benefits or limitations. This paper presents a phenomenological study exploring the lived experience of interpersonal communication within the context of problematic Internet use (PIU). Semi-structured in-depth interviews were conducted with six adults who self-identified with PIU and the resultant transcripts served as data for an Interpretative Phenomenological Analysis. Three super-ordinate themes emerged: 1) ‘Meeting interpersonal needs’ 2) ‘Interplay between two worlds: the virtual and the physical’ 3) ‘Online armour: the Internet as a form of protection.’ Participants relate the profound impact that the Internet has had and continues to have on their interpersonal lives and relationships. Whilst there are prominent threads of conflict, difficulty and distress, benefits, opportunities and enhanced social networks are also highlighted. The findings both support and contribute new aspects to the knowledge of PIU, and significantly, provide qualitative insight, which has been somewhat neglected in this field to date. The findings are examined in light of phenomenological ideas and their value in the understanding of PIU and interpersonal communication in the digital age, within the realm of Counselling Psychology and other related fields.